The Mental Condition of a Manipulative Personality Refelected in the Main Character in David Fincher’s Gone Girl (2014) - Muchammad Alyan Chafash Chafiidzul Umam; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This research aims to analyze Amy Dunne mental condition as a as a manipulative person in David Fincher’s Gone Girl.This research uses a qualitative descriptive method to analyze the film entitled